2023
DOI: 10.3390/healthcare11020171
|View full text |Cite
|
Sign up to set email alerts
|

Association between Migraine and Workplace Social Support in the Social Context of China: Using a Validated Chinese Version of the DCSQ

Abstract: Background: Workplace social support might have a protective function against migraine in the social context of China, as close co-worker relationships and collectivism are acknowledged as work values in Chinese society. Objectives: This paper aimed to analyse the association between migraine and workplace social support. The validity and reliability of the Chinese version of the Support scale of the Demand-Control-Support Questionnaire (DCSQ) used were also determined. Methods: Following international guideli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
(78 reference statements)
0
1
0
Order By: Relevance
“…These studies suggest that social support may play a role in decreasing migraine attacks as it was found to affect the anxiety and depression scores of patients with migraine. In a similar study, assessing the role of work social support in migraine among 607 Chinese bank workers, it was shown that high social support in workplace was associated with a 74% reduction of chance to be affected by migraine [ 64 ]. Co-worker support had the greatest protective effect against migraine among six aspects of workplace support.…”
Section: Social Agingmentioning
confidence: 99%
“…These studies suggest that social support may play a role in decreasing migraine attacks as it was found to affect the anxiety and depression scores of patients with migraine. In a similar study, assessing the role of work social support in migraine among 607 Chinese bank workers, it was shown that high social support in workplace was associated with a 74% reduction of chance to be affected by migraine [ 64 ]. Co-worker support had the greatest protective effect against migraine among six aspects of workplace support.…”
Section: Social Agingmentioning
confidence: 99%